2013
DOI: 10.3109/21681805.2013.861508
|View full text |Cite
|
Sign up to set email alerts
|

Diethylstilboestrol for the treatment of prostate cancer: past, present and future

Abstract: The aim of this review was to discuss the most recent data from current trials of diethylstilboestrol (DES) to identify its present role in advanced prostate cancer treatment as new hormonal therapies emerge. The most relevant clinical studies using DES in castration-refractory prostate cancer (CRPC) were identified from the literature. The safety, efficacy, outcomes and mechanisms of action are summarized. In the age of chemotherapy this review highlights the efficacy of oestrogen therapy in CRPC. The optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 89 publications
0
24
0
2
Order By: Relevance
“…The mechanism of action of DES remains uncertain because a 1-mg dose does not render some men castrate, and DES produces responses when used in CRPC. 170 Transdermal estradiol may provide similar cancer control with fewer side effects. 171 The ongoing PATCH clinical trial demonstrated similar rates of castrate levels of testosterone, PSA response, and side effects in 85 men treated with LHRH agonist and 168 men treated with 100 mcg/24-hour estrogen patches twice weekly.…”
Section: Secondary Hormone Therapy For Crpcmentioning
confidence: 99%
“…The mechanism of action of DES remains uncertain because a 1-mg dose does not render some men castrate, and DES produces responses when used in CRPC. 170 Transdermal estradiol may provide similar cancer control with fewer side effects. 171 The ongoing PATCH clinical trial demonstrated similar rates of castrate levels of testosterone, PSA response, and side effects in 85 men treated with LHRH agonist and 168 men treated with 100 mcg/24-hour estrogen patches twice weekly.…”
Section: Secondary Hormone Therapy For Crpcmentioning
confidence: 99%
“…After reviewing several major references , the panel recommended against the use of anti‐androgen monotherapy or oestrogen as first‐line treatment of castration‐naïve mPCa because, compared with ADT, inferior efficacy was observed from clinical settings.…”
Section: Resultsmentioning
confidence: 99%
“…For example, estrogens (and synthetic estrogens such as diethylstilbestrol) and androgens have immunosuppressive effects that affect both adaptive and innate immunity. [217][218][219][220] Nanoparticles, usually studied as a drug delivery method or biomedical imaging tool (e.g., metallic nanoparticles), are typically taken up by macrophage/monocyte cells and may act either as immunostimulants or as immunosuppressants and may have additional immune effects related to imaging methods such as MRI or μCT. 221 The unique physicochemical characteristics of nanoparticles influence their interactions with host's immune system and determine the overall immunotoxicologic profile.…”
Section: Cpg Oligodeoxynucleotidesmentioning
confidence: 99%